Metal-supported SOFC Fabricated by Tape Casting and Its Characterization: A Study of the Co-sintering Process - Zaka Ruhma; Keiji Yashiro; Itaru Oikawa; Hitoshi Takamura; ‪Tatsuya Kawada (Institute for Research and Community Services, Institut Teknologi Bandung, 2021)
Metal-supported SOFC consists of metallic and ceramic multilayers. Since the cell has to be flat, interaction between the layers that results in a flat sintered layer needs to be studied. The method used here was changing the starting materials through several experiments. Here, we highlight the effects of pore former in metal slurry on the sintered half-cell multilayer of a 430L metallic support, an NiO-8YSZ anode, and an 8YSZ electrolyte. The results show that by changing the amount of pore former in the 430L metal slurry changed the sinterability of the metal layer. This change of the sinterability of the metal support affected the final warpage state of the cell. This study aid in explaining the sintering phenomena between layers of metal-supported SOFCs.